Inversor Interleaved Bidirecional para Estações de Recarga de Veículos Elétricos do tipo V2G - ANDERSON DA SILVA VOLPATO (2023)
The transport sector is one of the biggest villains when it comes to the amount of greenhouse gases that are emitted every year into the Earth’s atmosphere, which has been causing major environmental impacts such as increasing the poor quality of the air we breathe and also changes different climates in different parts of the world. One of the ways to reverse this situation is to replace combustion vehicles (VC) with electric vehicles (EVs) that do not pollute the environment, however, for this, it will be necessary to overcome a great cultural and commercial barrier that was introduced 100 years before. From the viewpoint of incentives, there is a need for governments to distribute charging stations throughout the territory to popularize this new trend. With that, new research opportunities are been related to the use of electric vehicles operating as distributed generators (local and mobile) in addition to the already used photovoltaic DG - with the aim of improving energy quality. This dissertation presents the theoretical study and experimental application of the control of a system of two inverters in parallel interleaved for interface and voltage control of a main DC bus from a microgrid of an electric bicycle charging station with vehicle-to-grid (V2G) methodology when connected to the distribution grid. The implemented prototype was designed for a nominal power of 20 kW, however, in the laboratory, about 8 kW was reached by delimitation in the equipment used, nevertheless, the experimental results presented were more than sufficient to validate the stability and energy quality of the system operation for generalizing to nominal power, either injecting power into the electrical network or absorbing it.